2018
DOI: 10.3390/antiox7110157
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Glucose Levels in Cell Culture Media Determine Resveratrol’s Effects on Growth, Hydrogen Peroxide Production, and Mitochondrial Dynamics

Abstract: Resveratrol is a plant-derived polyphenol that has been widely studied for its putative health promoting effects. Many of those studies have been conducted in cell culture, in supra-physiological levels of oxygen and glucose. Resveratrol interacts with reactive oxygen species (ROS) as an antioxidant or pro-oxidant. Resveratrol affects the expression and activities of ROS-producing enzymes and organelles. It is therefore important to consider how cell culture conditions might determine the effects of resveratro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Trans-resveratrol, a phytochemical with strong antioxidant property, is naturally found in grapes, berries, and peanuts. The benefits of trans-resveratrol have been reported in various diseases, including cancer, cardiovascular diseases, diabetes mellitus, neurological diseases, obesity, and other conditions associated with oxidative stress and inflammation [1][2][3][4][5]. Chemically, trans-resveratrol is converted into cis-resveratrol by light and has a very low aqueous solubility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Trans-resveratrol, a phytochemical with strong antioxidant property, is naturally found in grapes, berries, and peanuts. The benefits of trans-resveratrol have been reported in various diseases, including cancer, cardiovascular diseases, diabetes mellitus, neurological diseases, obesity, and other conditions associated with oxidative stress and inflammation [1][2][3][4][5]. Chemically, trans-resveratrol is converted into cis-resveratrol by light and has a very low aqueous solubility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis is preliminarily supported by the evidence that in S. cerevisiae at low cellular energy status (0.1% of glucose), 10 μM of resveratrol diminished the cell viability (Madrigal‐Perez et al, ) and that at 0.5% of glucose, the same resveratrol concentration increased H 2 O 2 release (Ramos‐Gomez et al, ), which could enhance the oxidative damage in cells. Additionally, it has been recently reported that 10 μM of resveratrol decreases cell growth in mouse myoblast (C2C12) and human prostate cancer (PC3) under high oxygen conditions (18% of O 2 ) and a low concentration of glucose (5 mM), and this phenotype was accompanied by an increase in H 2 O 2 release rate (Fonseca et al, ). A comparison of two doses of resveratrol (0.00007% and 0.0143%) in Apc Min mice (colorectal carcinogenesis model) fed a high‐fat diet showed that a lower dose of resveratrol suppressed intestinal adenoma development more efficiently than a higher dose (Cai et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the effects of resveratrol with the mutant HIF‐1α at high glucose are similar to the effects observed with resveratrol and galactose (which only generates ATP through OXPHOS) (Fonseca et al, ), which suggests a possible association among mitochondrial respiration, resveratrol, and HIF‐1α activity. In addition, it has been reported that the resveratrol (10 µM) effects on hydrogen peroxide release, cell growth and the mitochondrial network in C2C12 mouse myoblasts and PC3 human prostate cancer cells are dependent on oxygen levels (5% and 18%) and glucose concentrations (5 and 25 mM) (Fonseca, Moradi, Valente, & Stuart, ). Although the association between resveratrol and HIF‐1α to exert toxic effects is not clear, a possible relationship with the glucose concentration is evident.…”
Section: The Relationship Between the Cytotoxic Effect Of Resveratrolmentioning
confidence: 99%
“…This article provides an overview of recent findings about the anti-PCa activity of different natural compounds (Figure 2, Table 1). [47][48][49][50][51][52][53][54]80,100,107,123,124,[135][136][137][138][139]161,163,164,186,190,191,212] The use of phytochemicals for PCa management offers several advantages. Firstly, natural products are safe and well tolerated, as well as usually economically affordable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, treatments aimed at blocking these pathways and/or shifting lactic acid fermentation towards mitochondrial oxidative phosphorylation have shown promise in reducing tumor growth [189]. In recent studies by Fonseca J et al, resveratrol was found to promote a shift towards mitochondrial oxidation in PCa cells concomitantly with the suppression of proliferation, and when this change was prevented by culturing tumor cells in glucose-free medium or via prolyl hydroxylase (PHD) inhibition-mediated stabilization of HIF-1α, the phenol did not affect oxidative phosphorylation and cell growth, indicating that the metabolic shift from glucose fermentation to oxidation is fundamental for its anti-cancer effects [190,191].…”
Section: Natural Compounds Impairing Metabolismmentioning
confidence: 94%